Escalate protein plates from legumes for sustainable human nutrition - Singh, Nisha; Jain, Priyanka; Ujinwal, Megha; Langyan, Sapna (Frontiers in Nutrition, 2022)
Protein is one of the important, foremost and versatile nutrients of food. The quantity and quality of protein are determinants of its nutritional values. Therefore, adequate consumption of high-quality protein is essential for optimal growth, development, and health of humans. Based on short-term nitrogen balance studies, the Recommended Dietary Allowance of protein for the healthy adult with minimal physical activity is 0.8 g protein/kg body weight (BW) per day. Proteins are present in good quantities in not only animals but also in plants especially in legumes. With the growing demand for protein, interest in plant proteins is also rising due to their comparative low cost as well as the increase in consumers’ demand originating from health and environmental concerns. Legumes are nutrient-dense foods, comprising components identified as “antinutritional factors” that can reduce the bioavailability of macro and micronutrients. Other than nutritive value, the physiochemical and behavioural properties of proteins during processing plays a significant role in determining the end quality of food. The term complete protein is referred to when all nine essential amino acids are present in the correct proportion in our bodies. To have a balanced diet, a right percentage of protein is required for our body. The consumption of these high protein containing foods will lead to protein sustainability and eradicate malnutrition. Here, we shed light on major opportunities to strengthen the contribution of diversity in legume crops products to sustainable diets. This review will boost awareness and knowledge on underutilised pretentious foods into national nutritional security programs.